Studying tactile sensitivity - population approach - Kozłowska, Agnieszka (Polskie Towarzystwo Antropologiczne, 1998)
The purpose of this study was to investigate the basic characteristics of threshold tactile sensitivity in man. The study involved the examination of over 1500 people aged from 7 to 85 years, including 300 adult subjects aged over 21 years. 55% of the population under study were females. Digital pulps of the subjects were examined with the Semmes-Weinstein monofilaments aesthesiometer. The variability range of touch sensation was determined and the mean value and standard deviations of tactile threshold in sex and age classes were calculated. The relationship of touch with age, sex, body mass and height and with social and economic factors was investigated by means of the analysis of variance. An attempt to assess the inheritability of tactile sensitivity was made. Finally, the adaptive meaning of the sense o f touch in man was discussed.